The Revelations of St. Birgitta of Sweden, Volume 4: The Heavenly Emperor's Book to Kings, The Rule, and Minor Works - Searby, Denis; Morris, Bridget; Searby, Denis; Morris, Bridget (Oxford University Press, 2015)
St. Birgitta of Sweden (1303-1373, canonized 1391) was one of the most charismatic and influential female visionaries of the later Middle Ages. Altogether, she received some 700 revelations, dealing with subjects ranging from meditations on the human condition, domestic affairs in Sweden, and ecclesiastical matters in Rome, to revelations in praise of the Incarnation and devotion to the Virgin. Her Revelations, collected and ordered by her confessors, circulated widely throughout Europe and long after her death. Many eminent individuals, including Cardinal Juan Torquemada, Jean Gerson, and Martin Luther, read and commented on her writings, which influenced the spiritual lives of countless individuals. Birgitta was also the founder of a new monastic order, which still exists today. She is the patron saint of Sweden, and in 2000 was declared (with Catherine of Siena and Edith Stein) co-patroness of Europe.Birgitta's Revelations present her as a commanding and dauntless visionary who develops a contemplative mysticism that is always interwoven with social engagement and a commitment to the salvation of the world. The varied styles of her revelations are dominated by frequent juxtapositions of memorable images and allegories that illustrate her fierce and fertile imagination, her sharp powers of observation and understanding, and her passionate and receptive storytelling powers.This fourth and final volume of the translation of the Revelations of St. Birgitta of Sweden, comprises The Heavenly Emperor's Book to Kings, The Rule, and minor works. While the complete collection of Birgitta's books—called Liber caelistis—ends with Books VII, the eighth book was added after her death. It was compiled by Alfonso of Jaen, and is prefaced by his own treatise, titled The Hermits Letter to Kings, which examines the ways in which revelations are tested and proven to be true visions conferred by the Holy Spirit. The translation is based on the recently completed critical edition of the Latin text and promises to be the standard English translation of the Revelations for years to come. , St. Birgitta of Sweden (1303-1373, canonized 1391) was one of the most charismatic and influential female visionaries of the later Middle Ages. Altogether, she received some 700 revelations, dealing with subjects ranging from meditations on the human condition, domestic affairs in Sweden, and ecclesiastical matters in Rome, to revelations in praise of the Incarnation and devotion to the Virgin. Her Revelations, collected and ordered by her confessors, circulated widely throughout Europe and long after her death. Many eminent individuals, including Cardinal Juan Torquemada, Jean Gerson, and Martin Luther, read and commented on her writings, which influenced the spiritual lives of countless individuals. Birgitta was also the founder of a new monastic order, which still exists today. She is the patron saint of Sweden, and in 2000 was declared (with Catherine of Siena and Edith Stein) co-patroness of Europe.Birgitta's Revelations present her as a commanding and dauntless visionary who develops a contemplative mysticism that is always interwoven with social engagement and a commitment to the salvation of the world. The varied styles of her revelations are dominated by frequent juxtapositions of memorable images and allegories that illustrate her fierce and fertile imagination, her sharp powers of observation and understanding, and her passionate and receptive storytelling powers.This fourth and final volume of the translation of the Revelations of St. Birgitta of Sweden, comprises The Heavenly Emperor's Book to Kings, The Rule, and minor works. While the complete collection of Birgitta's books—called Liber caelistis—ends with Books VII, the eighth book was added after her death. It was compiled by Alfonso of Jaen, and is prefaced by his own treatise, titled The Hermits Letter to Kings, which examines the ways in which revelations are tested and proven to be true visions conferred by the Holy Spirit. The translation is based on the recently completed critical edition of the Latin text and promises to be the standard English translation of the Revelations for years to come.